Drgania Prętów Prostych i Płyt Obłożonych Masami Skupionymi - Solecki, R. (Engineering Transactions, 1961)
On the basis of the Eq. (1.3.1) of the present paper, determining the proper transform of a product of two functions, general solution is given for steady-state vibration, stability and equilibrium of straight bars and plates with concentrated masses and a continuous mass. In addition to several algebraic equations, a numerical example is quoted concerning the determination of the fundamental frequency of free vibration of a square isotropic plate clamped along the entire contour and having a concentrated mass in the middle.